Development and Application of Geography Board Games as Education Tools - Mohd, Nurazila Atika; Mohd Najib, Sumayyah Aimi (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
Geography education is becoming increasingly worrying when the subject of Geography becomes an elective subject. Geography education is becoming less of interest is due to the extensive content of learning plus the lack of learning materials and complete materials such as interactive and humanistic teaching materials are needed to make learning more meaningful. Innovative steps must be taken to ensure the effectiveness of teaching and learning systems in educational institutions. As a result, the development of a Geography based board game was developed as an alternative to this problem. In addition, it aims to provide geography-related education to students, especially students from 1st to 3rd grades. The methodology used in this study is qualitative through observations, interviews and data analysis. The development of this board game uses the "Gamified System Development Process". The development of this game board consists of two main phases namely (1) goal building and (2) interactive design. Pioneer studies show that students show a deep interest in Geobox. Geobox consists of the main mechanisms of points, levels, challenges, game boards and rewards (gifts and charity). Development and production of the prototype board game "Geobox" which covers the subject of Malaysian entity in the Geography textbook form1 to 3 namely the topic of drains and bodies of water, the landforms, flora and fauna, transportation, man and the identification of Malaysia.